Analisis Praktik Bisnis Berbasis Digital Melalui Tinjauan Tingkatan Maslahah dalam Ekonomi Islam - Mursalmina, Mursalmina (Program Studi Perbankan Syariah FEBIII UIN Ar-Raniry, 2026)
This research aims to analyze the levels of Maslahah in digital business practices in Indonesia. The research method used is descriptive qualitative with a library research approach. Secondary data sourced from scientific journals and authoritative textbooks were analyzed using content analysis techniques. The results show that the implementation of the Maslahah concept serves as a moral compass to align technological innovation with sharia objectives (Maqashid Sharia). At the Dharuriyyah level, the main focus lies on the protection of the five main foundations (al-kulliyat al-khams). The Hajiyah level is observed through the increase in MSME empowerment, financial inclusion, and flexibility in transactions that eliminates difficulties (masyaqqah) in public economic mobility. Meanwhile, the Tahsiniyyah level relates to the refinement of ethics and aesthetics, such as improving user experience and transparency through blockchain technology.